THE DETERMINATION OF DEPRESSION AND ANXIETY LEVEL IN INDIVIDUALS WITH CHRONIC HEART FAILURE - OĞUZ, SIDIKA (PAKISTAN CARDIAC SOC, 2021)
Objective: This study was planned to assess the depression and anxiety level in individuals with Chronic Heart Failure (CHF). Methodology: A cross sectional study was conducted in a training and research hospital in Istanbul. The population of the study consisted of patients with CHF who stayed in the cardiology and internal medicine clinics between the months of March and June 2017. One hundred consecutive patients of CHF were included in the study. The Hospital Anxiety and Depression Scale (HAD) was used to assess the anxiety and depression level of the patients and other demographic and exploratory variables data was collected on a questionnaire. Results: The anxiety and depression was found in 62% and 84%, CHF patients respectively. The anxiety levels were found to be high in the individuals with no social insurance, females, primary school graduates and housewives. Also, the depression levels of the cases whose duration of disease was longer were found to be high. The anxiety levels were found to be high in the individuals with DM, with NYHA class 3- 4, using diuretic and performing salt restrictions. There was no statistically significant difference between both subscales in patients with hypertension, using beta blockers or anticoagulants, and exercising. Conclusion: In our study both anxiety and depression are found to be common in patients with CHF.
Keywords: chronic heart failure; anxiety; depression; PREVALENCE; PREDICTORS; DISORDER